2020
DOI: 10.1088/1755-1315/499/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Greenhouse Gases Following the Use of Peatlands for Agricultural Areas

Abstract: Peatlands with very high C contents are generally considered a source of greenhouse gas (GHG) emissions. This research aimed to quantify the changes in peatland characteristics and GHG emission from the conversion of peatlands to agricultural areas. Height of water table, pH, electrical conductivity (EC), redox potential (Eh), organic carbon (OC), hot water-soluble C, total-N, the concentrations of NH4 +, and NO3 −, soluble-Al, soluble- Fe, and the emission of CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The decrease in carbohydrates and increase in lignin contents with changes in land use from uncultivated peatlands to cultivated peatlands are in agreement with the concept of changes in the chemical structure of organic C contained in peatlands with agricultural activities. Several agricultural activities in peatlands, such as drainage, fertilizing and liming, enhance the decomposition process of organic C contained in the peats, which in turn causes a decrease in organic C with structures that are easily decomposed, such as carbohydrates and results in the accumulation of organic C that is resistant to biodegradation such as lignin (Saidy et al 2018;Saidy et al 2020).…”
Section: Diversity In Peatland Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in carbohydrates and increase in lignin contents with changes in land use from uncultivated peatlands to cultivated peatlands are in agreement with the concept of changes in the chemical structure of organic C contained in peatlands with agricultural activities. Several agricultural activities in peatlands, such as drainage, fertilizing and liming, enhance the decomposition process of organic C contained in the peats, which in turn causes a decrease in organic C with structures that are easily decomposed, such as carbohydrates and results in the accumulation of organic C that is resistant to biodegradation such as lignin (Saidy et al 2018;Saidy et al 2020).…”
Section: Diversity In Peatland Characteristicsmentioning
confidence: 99%
“…Hirano et al (2014) reported that CO2 emission of burned tropical peatlands observed through field measurement is in the range of 362-382 g C m -2 year -1 . Emissions of CO2 in tropical peatlands before and after land clearing for agriculture are 77-143 mg C m -2 h -1 or 674-1253 g C m -2 year -1 (Saidy et al 2020). Based on the monthly observation in the field, Wakhid et al (2017) found that CO2 emission from peat decomposition in a tropical peatland reached 1408 g C m −2 yr −1 .…”
Section: Methane and Carbon Dioxide Emissionsmentioning
confidence: 99%
“…These pHs were in the pH range of tropical peats reported previously. For example, tropical peatlands with land-uses that vary from uncultivated to rice-cultivated peats and undrained to drained peats have a pH in the range of 3.34 to 5.33 [14,15]. Tropical-forested peatlands with varying organic carbon content had a pH range of 3.95-4.16 [16].…”
Section: Peat Characteristicsmentioning
confidence: 99%
“…The drainage of tropical peatlands brings about alterations in soil biogeo-physicochemical, thereby influencing the release of CO 2 , CH 4 , organic acids and organic particulates. Moreover, the rate of carbon loss is expected to be affected by climate change (2), particularly from the establishment of oil palm through the drainage and conventional slash-and-burn technique (3,4).…”
Section: Introductionmentioning
confidence: 99%